Faire la fête à un grand esprit : les paradoxes du centième anniversaire de Claude Lévi-Strauss - Gadbois, Jocelyn (Anthropologica, 2014)
This article analyzes various forms of homage organ ized in Paris for the Claude Lévi-Strauss hundredth anniver sary, particularly articles in the media and the special event at the musée du quai Branly. The author notes that these homages speak out of both sides of their mouths; not only do they try to honour the man and his wisdom, but they also focus on his death. This kind of sacrifice allows those who think they are his heirs to share a Claude Lévi-Strauss’ fragment, for them to do with as they saw fit. These retakes can be of a different nature, especially political.